Crop Wild Relatives as Germplasm Resource for Cultivar Improvement in Mint (Mentha L.) - Vining, Kelly J.; Hummer, Kim E.; Bassil, Nahla V.; Lange, B. Markus; Khoury, Colin K.; Carver, Dan (Frontiers in Plant Science, 2020)
Mentha is a strongly scented herb of the Lamiaceae (formerly Labiatae) and includes about 30 species and hybrid species that are distributed or introduced throughout the globe. These fragrant plants have been selected throughout millennia for use by humans as herbs, spices, and pharmaceutical needs. The distilling of essential oils from mint began in Japan and England but has become a significant industrial product for the US, China, India, and other countries. The US Department of Agriculture (USDA), Agricultural Research Service, National Clonal Germplasm Repository (NCGR) maintains a mint genebank in Corvallis, Oregon. This facility preserves and distributes about 450 clones representing 34 taxa, hybrid species, advanced breeder selections, and F1 hybrids. Mint crop wild relatives are included in this unique resource. The majority of mint accessions and hybrids in this collection were initially donated in the 1970s by the A.M. Todd Company, located in Kalamazoo, Michigan. Other representatives of diverse mint taxa and crop wild relatives have since been obtained from collaborators in Australia, New Zealand, Europe, Vietnam, and the Czech Republic. These mints have been evaluated for cytology, oil components, Verticillium wilt resistance, and key morphological characters. Pressed voucher specimens have been prepared for morphological identity verification. An initial set of microsatellite markers have been developed to determine clonal identity and assess genetic diversity. Evaluation and characterization includes essential oil content, disease resistance, flowering, and other traits for potential breeding use. These accessions can be a source for parental genes for enhancement efforts to produce hybrid lines, or for breeding the next generation of cultivars for agricultural planting. Propagules of Mentha are available for distribution to international researchers as stem cuttings, rhizome cuttings, or seed, which can be requested through the GRIN-Global database of the US National Plant Germplasm System, subject to international treaty and quarantine regulations. Plant breeders at private and public institutions are using molecular analysis to determine identity and diversity of the USDA mint collection. Marker assisted selection will increase in importance of specific genotypes for mint breeding programs.